Activity of Ethanol Extract and Fraction Products Leaves Manilkara kauki as Inhibitors Tyrosinase Enzyme - Zakri, Dwika Febriana; Putri, Dwi Hilda; Irdawati, Irdawati; Angelina, Marissa (Jurnal Biologi Tropis, 2025)
Currently, cosmetics made from chemical (synthetic) ingredients are in demand by the public because they can whiten the skin by inhibiting the formation of melanin, but the lack of public knowledge about the impact of excessive use has encouraged the need for natural ingredients as tyrosinase inhibitors that are safer than synthetic ingredients. This study aims to test the potential of secondary metabolite compounds in M. kauki leaves as inhibitors of tyrosinase enzyme activity by determining the IC50 value. This assay utilizes L-tyrosine and arbutin as positive control substrates, with UV-Vis spectrophotometric absorption measurements taken at a wavelength of 470 nm. The findings revealed that the buthanol fraction exhibited the highest tyrosinase enzyme inhibition, with an IC50 of 189,72 μg/mL. This was followed by the ethanol extract with an IC50 of 191,97 μg/mL, the hexane fraction at 381.50 μg/mL, and the ethyl acetate extract with an IC50 of 448.986 μg/mL. All samples displayed strong inhibitory activity, outperforming arbutin as a positive control, which had an IC50 value of 831.51 μg/mL.